Assessing the Impact of Collective Marketing of Paddy Rice in Innovation Platforms by Smallholder Producers in Benin - Arouna, A. (IntechOpen, 2018)
Market access is a major constraint of smallholder rice producers in sub-Saharan Africa (SSA). There is increasing evidence that acting collectively offers one way for smallholders to participate more efficiently in the market. This chapter aimed to identify the determinants of participation in collective marketing of rice in innovation platforms in Benin and quantify its impact on household income and food security. Unlike previous studies, we used the local average treatment effect parameter to assess the impact of collective marketing of rice. Data were collected from a random sample of 257 smallholder rice producers. Results showed that participation in collective marketing increased the income of rice farmers on average by USD 148/ha. Main determinants of participation in collective marketing of rice were membership in a farmer group, training, and agreement on price. This chapter concludes that better training and well-functioning farmer groups sustain the impact of collective marketing of rice on food security.